Lost Work Due to Burn-Related Disability in a US Working Population - Jacob M. Dougherty; Hannan A. Maqsood; Christopher J. Rittle; Eva S. Blake; Zhaohui Fan; Bryant W. Oliphant; Mark R. Hemmila; Naveen F. Sangji (European Burn Journal)
Background: Burn injuries can require hospitalization, operations, and long-term reconstruction. Burn-injured patients can experience short- or long-term disability. We investigated lost workdays (LWDs), short-term disability (STD), and long-term disability (LTD) in the 12-month period following a burn injury. Methods: An observational cohort study was conducted using a commercial claims database, IBM® MarketScan®. Patients aged ≤65 years with an ICD-10 burn diagnosis from 2018 to 2019 were included. The International Classification of Diseases, 10th Revision (ICD-10), procedure and Current Procedural Terminology (CPT) codes were used to identify patients undergoing burn-related operations. Patients were mapped to data tables for LWDs, STD, and LTD for the 12 months pre- and post-injury. Paired t-tests were employed to compare the pre- and post-injury outcomes. Results: We identified 1745 patients with burn diagnoses. Of those, 263, 1449, and 1448 patients had data available for LWDs, STD, and LTD, respectively. STD and LTD were reported by 8.1% and 0.0% of patients in the 12-month period pre-injury, respectively, and 20.3% and 1.0% of patients in the 12-month period post-injury, respectively. Average days of STD increased from 3.70 to 9.34 days following injury. Conclusions: Burn injuries are associated with increased STD and LTD utilization. Quantifying the impact of burn injuries on patients’ work will help us understand the economic implications of burns, which is a key area in burn research.